MODEL REALIZED VOLATILITY UNTUK SELEKSI SAHAM PADA JAKARTA ISLAMIC INDEX DI INDONESIA - Josep Ginting (Indonesian Journal of Economics and Business, 2011)
Capital market conditions in Indonesia have changed rapidly since the 1998 when economic crisis started, giving rise to many changes both in the form of data available on the Indonesia Stock Exchange and the pattern of daily transactions on the Indonesia Stock Exchange. These changes led to one of them is a pattern of highly speculative transactions that avoid investments based on Islamic Principle. According to those conditions, considered to find and formulate the best model to  measure the volatility  of stock prices in Islamic stocks selection process.            The Research was based on the phenomenon in the stock market experienced a volatile stock price changes while the EMH theory particularly Weak Form Efficiency Hypothesis says that all past price is reflected in current prices which means there is no market anomalies. The result is used to know market efficiency in Indonesia in other to decide whether volatility measurement is needed or not. Beside using theory of EMH, this research also used market micro structure theory.            This research set volatility modeling by performing the steps of mathematical and statistical test. The steps taken is to test the normality of the volatility estimation results compare to the original price during the last 10 trading days, then tested also whether there is the effect of lagged positive return and/or lagged negative return as independent variable to volatility tools as dependent variable by doing a regression analysis to determine whether the theory of EMH can be fully implemented in Indonesia and if not then the necessary measures volatility. The result shows that lagged positive return and/or lagged negative return did not affect the volatility of stocks price significantly. Finally, used mathematical calculations on the formation of the desired volatility models by choosing the best estimate of the tools between the ARIMA and ARFIMA, then applied the best tool to test model of realized volatility.           The best volatility measurement model based on observable data is realized volatility. Realized volatility model is used to select the stocks for Jakarta Islamic Index.